Quality, phenolic compounds, and antioxidant activity of ’Tupy’ and ’Guarani’ blackberries stored at different temperatures - Soethe, Cristina; Steffens, Cristiano André; Amarante, Cassandro Vidal Talamini do; De Martin, Mariuccia Schlichting; Bortolini, Anderson Jose (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of storage temperature on the quality maintenance, content of phenolic compounds, and antioxidant activity of 'Tupy' and 'Guarani' blackberry (Rubus sp.) fruit. Fruit were stored at 0, 5, 10, and 15°C. After five days of storage, fruit were evaluated for the following parameters: skin color, respiratory rate, weight loss, force to compression, titratable acidity (TA), soluble solids content (SSC), SSC/TA ratio, incidence of decay, total phenolic compounds (TPC), and total antioxidant activity (TAA). In both cultivars, the temperature increase caused boosting of respiratory rate, weight loss, and incidence of decay, as well as reduction in SSC and TA, especially at temperatures over 5°C. There was no effect of temperature on skin color of 'Tupy'. In 'Guarani' blackberries, chroma and hue angle decreased with temperature. Fruit force to compression, in both cultivars, augmented by temperature increasing between 0 and 5°C. Values of TPC and TAA augmented with increasing of temperature in both cultivars. Fruit storage at 5ºC for both cultivars yields firmer fruit and higher TA, while allowing the increase of TPC and TAA without impairing fruit taste and visual appearance.